Effect of different thawing methods on the quality of goat liver - Hasan, R; Kathun, H; Khatun, M; Azad, MAK; Khan, M (Meat Research, 2024)
The experiment was conducted to find out the effect of different thawing methods like ambient temperature thawing, refrigerator thawing and tap water thawing on the quality of goat liver. Sensory evaluation, proximate components, physico-chemical quality, biochemical properties and microbiological tests. Six goat livers were collected from a local slaughterhouse. Liver samples were preserved under freezing condition (-20°C) for 3 months after fresh evaluation. After evaluation of thawed liver, color, odor, juiciness, and tenderness were significantly (P<0.05) different with maximum values of color and odor found in refrigerator thawing while maximum juiciness and tenderness value found in ambient temperature thawing. DM and Ash contents were not significantly differed (P>0.05); however, the highest value found in refrigerator thawing within the three thawing methods. CP content was significant (P<0.05) different among the different thawing methods. EE content differed significantly (P<0.05), although less amount of EE content was found in refrigerator thawing. There was no significant (P>0.05) variation of pH value on studied thawing methods. Thawing loss, WHC and colour measurement significantly (P<0.05) differed with the different thawing methods, while thawing loss of tap water thawing, WHC value of ambient temperature thawing and colour value of refrigerator thawing were found in maximum level. TBARS value was significantly varied among the different thawing methods where the minimum result found in tap water thawing but maximum result found in ambient temperature thawing. TVC, TCC and TYMC comparatively more number found in ambient temperature thawing but less number found in refrigerator thawing. The lowest number of microbial counts found in refrigerator thawing. It may conclude that refrigerator thawing is the best thawing method to determine the quality of goat liver than others in this experimental condition.